UMP awarded prestigious Motorola Solutions Foundation grant - Nurul Hazlina, Noordin (2019)
Universiti Malaysia Pahang (UMP) was recently awarded the prestigious Motorola Solutions Foundation grant for its “MySTEM Project: A STEM Outreach Program” at a ceremony in Penang on March 1, 2019.